2023
DOI: 10.1186/s13102-023-00634-2
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity exercise prescription guided by heart rate variability in breast cancer patients: a study protocol for a randomized controlled trial

Abstract: Background Breast cancer is a chronic disease with a large growth in its treatments, prognosis, improvements, side effects and rehabilitation therapies research. These advances have also highlighted the need to use physical exercise as a countermeasure to reduce the cardiotoxicity of pharmacological treatments, increase patients' strength and quality of life and improve body composition, physical condition and mental health. However, new investigations show the need for a closed exercise indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…With the volume of patients, a confidence level of 95%, a precision of 5% and an expected proportion of losses of 15% (women who do not complete the study), were obtained for a sample of N = 59 patients. This is considered optimal as it is consistent with previous studies related to the same topic [24][25][26].…”
Section: Participantssupporting
confidence: 82%
“…With the volume of patients, a confidence level of 95%, a precision of 5% and an expected proportion of losses of 15% (women who do not complete the study), were obtained for a sample of N = 59 patients. This is considered optimal as it is consistent with previous studies related to the same topic [24][25][26].…”
Section: Participantssupporting
confidence: 82%
“…In this perspective, functional capacity is considered of paramount importance to ensure greater adherence and response to treatment, as well as to improve morbidity and mortality indicators [ 27 ]. It is explained that maintaining muscle mass and improving oxygen transport may favor a decrease in sympathetic tone and an increase in vagal tone, consequently decreasing heart rate (HR) at rest and increasing HRV and baroreflex sensitivity [ 14 , 37 39 ]. This effect may be opposite in the absence of exercise practice [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, according to the guidelines ( 7 , 39 , 40 ), patients were advised to engage in moderate physical activity, but no upper limit was mentioned. Even though, none of the BEGYN-1 study patients showed any sign of overexertion or other negative side effects of too much physical activity, further research is needed to individualize recommendations for the level of physical activity to aim for ( 50 , 51 ). The increased physical activity and fitness achieved in the BEGYN-1 study might have multiple other consequences that are known to be associated with increased physical activity in breast cancer patients, e.g., increased bone health ( 52 ), reduced cancer related fatigue ( 53 ), and reduced cancer related cognitive impairment ( 54 ).…”
Section: Discussionmentioning
confidence: 99%